Agar- agar as stabilizer in ice cream Anna Victoria F. Agbayani ; Sonia Y. De Leon, adviser. - Agbayani, Anna Victoria Flor; De Leon, Sonia Y. (1964., 1964)
(NO ABSTRACT)
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Marine algae